Adapt or Die? Resilience Discourse and the Shifting Contours of Humanitarian Morality (2022)
The epistemic terrain of humanitarian morality has undergone a profound paradigmatic transformation in recent years. The turn towards “resilience” as a structuring principle in aid programmes has produced new modes of governance that challenge what I call the moral exceptionalism of humanitarianism’s mandate. This article traces the trajectory of moralism in humanitarian studies, exploring how the productive tension between contrapuntal readings of humanitarianism as moral intent or biopolitical care is transcended by the resilience paradigm’s ontological vision of an intrinsically fragile and vulnerable world. Contrary to theoretical critiques of resilience as an extension of neoliberal tenets to global governance, I draw on the context of the Syrian refugee crisis in Jordan to argue that resilience humanitarianism has in fact prompted a return to state welfare as the final guarantor of refugee rights.